The Influence of Promotion Strategy and Scarlett Whitening Product Quality on Students' Purchasing Decisions - Hermina, Sitti; Radji, Djoko Lesmana; Isa, Ramlan Amir (International Journal of Multidisciplinary Applied and Science Research, 2025)
The selection of a good promotional strategy makes the product more known to consumers and good product quality encourages consumers to choose the product. This study aims to determine 1) the effect of promotional strategy and product quality on purchasing decisions for Scarlett Whitening products among students. The research method uses a sample size of 92 students majoring in management, Faculty of Economics, State University of Gorontalo with a quantitative approach to this study. The results of the study indicate that partially the promotional strategy does not have a significant effect on purchasing decisions, but the different thing is for product quality on purchasing decisions for Scarlett Whitening. Promotion and product quality are able to encourage purchasing decisions for this product